Analysis of the Risk of Profit Loss in Papaya Farming Affected by Yellow Mosaic Disease - Ridha Novanda; Mimi Sutrawati; Dwi Wahyuni Ganefianti (Newinera Publisher, 2021)
Profit loss is a phenomenon caused by the loss of most of the harvest resulting in operating costs greater than the revenue earned. This phenomenon deserves to be analyzed the risk of losses that will be obtained due to pests and plant diseases. So that in this study an analysis of the risk of Profit loss due to yellow mosaic disease on papaya calina was carried out. This research was conducted in October 2020 in Bengkulu Province on 31 Calina Papaya farmers. The location selection was carried out purposively based on the existence of the Calina papaya garden. Meanwhile, the selection of respondents was carried out using the Snowball sampling method in several districts in Bengkulu Province. Data analysis was carried out to determine the Profit loss. Based on the results of the analysis, it was found that there were differences in the benefits of papaya calina which were attacked by the Yellow Virus Mosaic and those that were not attacked by the Yellow Virus Mosaic. Profit loss for a year is Rp 9,135,203,-. This value is a big value, so farmers must handle this disease better.